Analysis of Free Indirect Discourse Narratives in the Works of Austen, Joyce, and Kingston - Lestari Manggong (Universitas Sanata Dharma, 2017)
Language, with the complexity of its structure, can be problematic in terms of interpreting works of literature. This essay discusses the problems perceived in the process of interpretation of free indirect discourse narratives in Jane Austens Pride and Prejudice and Emma, James Joyces A Portrait of an Artist as a Young Man and The Dead, and Maxine Hong Kingstons Tripmaster Monkey. Narratives with free indirect discourse opens up possibility of misinterpretation caused by the misconception of whose point of view the story is told. By looking at the works within the concept of narratology by Chatman (1978) and Prince (2003), such narrativeswhich apply the viewpoint of omniscient narratorscause ambiguity to the voice of external and internal focalisers. This is due to the fact that the use of such narratives blends the two types of focalisations. The findings of this research lead to an argument that through external focalisation, the view becomes objective. Yet through internal focalisation, the view tends to become subjective as it is infiltrated by the characters view. Such an argument then gives way to a conclusion that narratives with free indirect discourse gives effect to irony in the story-telling process of the works discussed. Keywords: free indirect discourse, narratology, focalisation